2020
DOI: 10.3390/ijerph17186470
|View full text |Cite
|
Sign up to set email alerts
|

Health and Well-Being of Adolescents in Different Family Structures in Germany and the Importance of Family Climate

Abstract: The family is of exceptional and lifelong importance to the health of adolescents. Family structure has been linked to children’s and adolescents’ health and well-being; a nuclear family has been shown to be indicative of better health outcomes as compared with a single-parent family or a step-family. Family climate is rarely included in studies on children’s and adolescents’ health and well-being, albeit findings have indicated it is importance. Using data from n = 6838 students aged 12–13 years from the Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 68 publications
(94 reference statements)
4
32
0
3
Order By: Relevance
“…Thus, a family structure is an important determinant of students' mental health not only during the COVID-19 pandemic ( 64 , 65 ). It is well-known that the family has an irreplaceable place in students' lives, while the presence of both parents is an essential aspect of cohesion, stability and support ( 66 ). Gray et al ( 67 ) also emphasized that students reporting sufficient time spent with family members and highest level of love and connectedness, as well as those living in a two-parent family, were happiest.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a family structure is an important determinant of students' mental health not only during the COVID-19 pandemic ( 64 , 65 ). It is well-known that the family has an irreplaceable place in students' lives, while the presence of both parents is an essential aspect of cohesion, stability and support ( 66 ). Gray et al ( 67 ) also emphasized that students reporting sufficient time spent with family members and highest level of love and connectedness, as well as those living in a two-parent family, were happiest.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have confirmed that the association between family structure and health is at least partially mediated by the family’s SEP [ 34 , 35 ]. Furthermore, several previous studies have examined the associations between the psychosocial characteristics of the family and SRH, such as family cohesion, parenting behavior, parental support, parent-adolescent relationships and communication [ 19 , 36 39 ]. Moreover, Breidablik et al [ 38 ] reported that low general well-being and low life satisfaction of the mother or father were important parental factors associated with lower SRH in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Parental smoking, smoking in the household and parental obesity were found to be important parental predictors for poor SRH in adolescents [ 38 , 40 ]. Moreover, SEP is linked to several familial determinants [ 33 , 41 – 45 ], including family structure [ 39 , 46 ], parenting behavior [ 43 , 44 ] and parental stress [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate substantive preparation of medical professionals (physicians, physiotherapists, nurses and midwives) to their profession, which commenced during their studies and continued throughout their postgraduate education, will signi cantly affect the health of those people who come to clinics and hospitals. Education and knowledge about health promoting behaviour should be expanded with regard to the existing dangers of losing health, aspects affecting our health, and factors which contribute to diseases [2,3,6,20,24].…”
Section: Discussionmentioning
confidence: 99%
“…Without doubt, health is the most important and precious value, as only a healthy person can fully bene t from all aspects of both professional and private life, including entertainment and sport. Therefore, health has a great in uence on the quality and lifestyle of an individual, their social contacts and economic possibilities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%